ANALYSIS OF THE DYNAMICS OF INFLUENZA IN A FAMILY PRACTICE CLINIC (Ustozlar uchun, 2026)
This article analyzes the dynamics of influenza disease prevalence in a family clinic setting. The study examined the seasonal variation of influenza in the population, the incidence rate by age group, and the effectiveness of preventive measures. According to the analysis results, a significant increase in flu cases was observed during the fall-winter season. It was also noted that the incidence rates were highest among the working-age population. Vaccination, adherence to sanitary and hygiene rules, and raising public health literacy are of great importance in the prevention of influenza.